Live birth rate following frozen-thawed blastocyst transfer is higher in high-grade day 6 blastocysts than in low-grade day 5 blastocysts - Shi, Wenhao; Zhou, Hanying; Chen, Lijuan; Xue, Xia; Shi, Juanzi (Frontiers in Endocrinology, 2023)
Background Day 5 (D5) blastocysts are generally given priority to transfer than day 6 (D6) blastocysts; however, which one should be prioritized to transfer when only low-grade D5 and high-grade D6 blastocysts are available? Methods A large retrospective cohort study was carried out to evaluate the live birth rate (LBR) following D5 and D6 blastocysts in single frozen-thawed blastocyst transfer (FBT) during January 2014 and December 2018. A multivariate logistic regression was conducted to evaluate the combined impact of expansion day (D5 and D6) and blastocyst quality (high grade/low grade) on LBR, accounting for the potential confounding factors. The biopsied blastocysts from a consecutive PGT-A case series during February 2013 to December 2021 were analyzed in a supplementary study. Results The LBR achieved in high-grade D6 blastocyst transfer was significantly higher than that in low-grade D5 blastocyst transfer (50.43% vs. 40.70%, aOR 1.54, 95% CI 1.05–2.26, p = 0.027). There were no significant differences in preterm birth rate, very preterm birth rate, mean live birth weight, and birth weight <1,500 g and >4,000 g between the two cohorts. As for aneuploidy analysis in PGT, there were 54.55% of euploid blastocysts (30/55) among high-grade D6 blastocysts, significantly higher than the 41.39% of euploid blastocysts (565/1,365) among low-grade D5 blastocysts (p < 0.001). Conclusions Our data suggest that D6 blastocysts with high morphology grading are preferred than D5 blastocysts with low morphology grading when selecting blastocyst transfer to shorten the time of conception.